(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
In recent years, technology and artificial intelligence (AI) have been rapidly developing, causing fundamental changes in the field of education, in particular in the process of learning foreign languages. The process of learning English is now not limited to traditional lessons, but also allows learning with the help of digital technologies, mobile applications and AI-based educational platforms. This article analyzes the impact of AI technologies on English language learning, including the role of personalized learning, speech recognition, virtual and augmented reality, and AI-based chatbots. It also discusses the advantages and limitations of AI-based learning compared to traditional methods. Research findings show that AI-integrated language learning methods are very effective, but technology and human factors must be combined to achieve maximum results.